Boundary Crossing in Hiroshima Oral History Education: Co-Constructing Sustainable Peace Practices through the Paintings of the Atomic Bomb Project - Kenji Nakamura (IAIN Madura, 2026)
The transmission of war memories is indispensable for achieving Sustainable Development Goal 16 (SDG 16): Peace, Justice and Strong Institutions. However, in oral history education, the experiential and sociocultural boundary between aging war survivors and contemporary students poses a significant challenge, leading to psychological burden and loss of opportunity for critical analysis. This study aims to clarify the learning mechanisms through which students and testifiers overcome this boundary to co-construct a new historical narrative of peace and form a sustainable community of peace practice. A secondary analysis was conducted on two cases from the Paintings of the Atomic Bomb (PAB) project in Hiroshima, employing the four learning mechanisms of boundary crossing (i.e., identification, coordination, reflection, and transformation) proposed by Akkerman and Bakker (2011). The results demonstrated that simply listening to testimonies leads to the reinforcement of the boundary; therefore, crossing it necessitates the coproduction of the PAB as a boundary object, together with a clear concrete operational goal. Through this triadic relationship mediated by the boundary object, participants coordinate communication, proactively reflect on their respective roles, ultimately transform perspectives, and co-construct a new historical narrative of peace.